T cell recognition of stress-induced post-translational modifications - Vaghela, Poonam (2022)
Background: Citrullination is the post-translational modification of arginine to citrulline mediated by peptidylarginine deiminases (PADs). We have previously shown that vaccination with citrullinated peptides from vimentin and α-enolase which are presented on HLA-DR4 or -DP4 in tumour cells mediate strong anti-tumour responses [1, 2]. This response is dependent upon autophagy and presentation of citrullinated peptides on MHC-II. Cytotoxic CD4 T cells can directly kill tumours expressing MHC-II and cognate peptide. As most tumours do not express MHC-II unless induced to do so by IFNγ we propose that citrullination is a normal stress response but that citrullinated epitopes are only presented on viable cells in the presence of inflammation.